IPO VS. PRIVATE PLACEMENT – DECISION TO MAKE TO ATTRACT THE FINANCIAL RESOURCES - N. Krylova (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
Advantageous and disadvantageous of private and public offering by the Ukrainian companies are analyzed by the author. Presented comparative analysis and initial costs analysis made by the author allows the Ukrainian companies to make the ‘wiser’ selection among available options.